1984
DOI: 10.1073/pnas.81.19.5941
|View full text |Cite
|
Sign up to set email alerts
|

Thyrotropin controls transcription of the thyroglobulin gene.

Abstract: The availability of rat thyroglobulin cDNA clones was exploited to study the regulation of thyroglobulin gene transcription by thyrotropin (TSH). Groups of rats were subjected to treatments leading to reduction or increase in the rat serum TSH (rTSH) levels. Thyroid gland nuclei were isolated, incubated in vitro in the presence of 32P-labeled uridine triphosphate, and thyroglobulin transcripts were quantitated by hybridization to immobilized rat thyroglobulin cDNA clones. Transcription of the thyroglobulin gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
43
2

Year Published

1985
1985
2004
2004

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 116 publications
(54 citation statements)
references
References 34 publications
7
43
2
Order By: Relevance
“…Thyroid follicular cell differentiation and thyroid function in the adulthood are maintained by the tonic TSH stimulation from the pituitary gland (36,41,42). TSH receptor activation leads to an increase in cAMP levels that ultimately induces Tg gene expression in vivo (36,43).…”
Section: Discussionmentioning
confidence: 99%
“…Thyroid follicular cell differentiation and thyroid function in the adulthood are maintained by the tonic TSH stimulation from the pituitary gland (36,41,42). TSH receptor activation leads to an increase in cAMP levels that ultimately induces Tg gene expression in vivo (36,43).…”
Section: Discussionmentioning
confidence: 99%
“…The nature of the other proteins whose synthesis is modified in the presence of thyrotropin (and cyclic AMP) remains to be determined. The 300000-M, product might be thyroglobulin, a protein which has been shown to be induced by thyrotropin at the genetic level [36].…”
Section: Discussionmentioning
confidence: 99%
“…Experiments conducted in the rat had shown that a normal level of circulating TSH is required to sustain transcription of the Tg gene at a detectable level in the intact animal (115). This effect of TSH on the transcription of the Tg gene had also been shown to be mediated by cAMP as it could be reproduced by forskolin in the intact rat tissue incubated in vitro (116).…”
Section: Transcriptional Regulation Of Thyroid-specific Genesmentioning
confidence: 99%